1994
DOI: 10.1530/eje.0.1300612
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic and islet blood flow in F1-hybrids of the non-insulin-dependent diabetic GK-Wistar rat

Abstract: Previous studies have indicated that various conditions under which an increased functional load is posed on the pancreatic islets, e.g. partial pancreatectomy and continuous glucose infusions, may influence the microcirculation of the pancreas. To investigate further the effects of elevated functional demand on the islets, the blood perfusion of the whole pancreas and the pancreatic islets was measured with a microsphere technique in an animal model presenting impaired glucose tolerance and mild hyperglycemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
31
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 16 publications
6
31
0
Order By: Relevance
“…In general, increased functional demands on the pancreatic islets are associated with an islet blood hyperperfusion [1]. In line with this, an increased islet blood flow is seen in Type 2 diabetic GK rats and their F 1 -hybrids, but also disturbances in islet blood flow regulation [10,11,13,47,48]. The decreased islet blood perfusion that we observed in normal rats in response to hypoglycaemia is theoretically advantageous during hypoglycaemia, as it could reduce the dispersal of insulin to the peripheral circulation, thereby diminishing the degree of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In general, increased functional demands on the pancreatic islets are associated with an islet blood hyperperfusion [1]. In line with this, an increased islet blood flow is seen in Type 2 diabetic GK rats and their F 1 -hybrids, but also disturbances in islet blood flow regulation [10,11,13,47,48]. The decreased islet blood perfusion that we observed in normal rats in response to hypoglycaemia is theoretically advantageous during hypoglycaemia, as it could reduce the dispersal of insulin to the peripheral circulation, thereby diminishing the degree of hypoglycaemia.…”
Section: Discussionmentioning
confidence: 75%
“…Although neuropathic changes are known to occur in diabetic GK rats [49,50], an even more pronounced decrease in islet blood flow occurred in the GK rats than in normal rats. Of interest, diabetic GK rats and their hybrids have been shown to have an increased islet blood flow during normal conditions dependent on a glucose-dependent mechanism mediated by the vagus nerve [11,13]. Whether also the more pronounced hypoglycaemia-induced decrease in islet blood flow in GK rats compared to normal rats, relates to changed vagal nervous activity is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study now shows that the islet as an organ seems to be threatened by factors that affect vascular function. The increased functional demand aged islets face may lead to increased islet blood flow (43,44), which in turn may trigger increased capillary pressure and compromise islet microcirculation (45). In addition, with aging, the vascular phenotype makes a proinflammatory shift that contributes to endothelial dysfunction (46).…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory mechanisms that control islet blood flow are complex and include neural, hormonal, and local mechanisms that are independent of the surrounding exocrine pancreas (5). It has been reported that islet blood flow is altered in rodent models with type 1 (6) or type 2 diabetes (7,8), obesity (9 -11), and hypertension (12). Although it has been suggested that changes in islet blood flow may be closely relevant to changes in islet function and metabolism, the relationship between flow and function is not fully understood.…”
mentioning
confidence: 99%